2016
DOI: 10.1080/2162402x.2016.1160182
|View full text |Cite
|
Sign up to set email alerts
|

AIM2 inflammasome mediates Arsenic-induced secretion of IL-1 β and IL-18

Abstract: Chronic sterile inflammation has been implicated in the pathogenesis of many cancers, including skin cancer. Chronic arsenic exposure is closely associated with the development of skin cancer. However, there is a lack of understanding how arsenic induces chronic inflammation in the skin. Interleukin-1 family cytokines play a central role in regulating immune and inflammatory response. IL-1α, IL-1β and IL-18 are three pro-inflammatory cytokines in IL-1 family. Their secretion, especially the secretion of IL-1β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, the NLRP3 rs1539019 C allele additively and multiplicatively interacted significantly with the total urinary arsenic concentration in the increased risk of RCC. The relationships identified in this study may result from the effect of arsenic on NLRP3 inflammasome activation, which alters caspase-1 and IL-1β levels 11 and the risk of developing RCC. Perhaps, NLRP3 rs1539019 affects the gene expression or linkage disequilibrium of other functional gene polymorphisms, which enhances the risk of RCC.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, the NLRP3 rs1539019 C allele additively and multiplicatively interacted significantly with the total urinary arsenic concentration in the increased risk of RCC. The relationships identified in this study may result from the effect of arsenic on NLRP3 inflammasome activation, which alters caspase-1 and IL-1β levels 11 and the risk of developing RCC. Perhaps, NLRP3 rs1539019 affects the gene expression or linkage disequilibrium of other functional gene polymorphisms, which enhances the risk of RCC.…”
Section: Discussionmentioning
confidence: 95%
“…One study has shown that arsenic trioxide (As 2 O 3 ) could induce nonalcoholic steatohepatitis, increase autophagy, NLRP3 inflammasome activation, and lipid accumulation, which leads to lipid-related gene dysregulation 14 . Another study demonstrated that arsenic enhanced the AIM2 inflammasome activation to increase IL-1 β/ IL-18 production 11 . In contrast, Ahn et al 15 demonstrated that arsenic could inhibit the activation of the NLRP3 inflammasome in macrophages in response to lipopolysaccharide treatment, which attenuated the elevation of serum IL-1β in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most inflammasome receptors, potential phosphorylation sites have been reported (see ref [47] for a comprehensive overview), but for many of them, it is still unclear whether phosphorylation affects their activity. For example, it has been reported that NLRP1 and AIM2 might serve as substrates for protein kinase R (PKR) [58,59], but it is still debated whether the kinase activity of PKR is required for their activation [60,61]. With respect to the topic of the present review, however, tyrosine phosphorylation has mainly been described for the adaptor molecule ASC and for members of the NLRP family.…”
Section: Phosphorylation As a Regulator Of Inflammasome Activationmentioning
confidence: 95%
“…Moreover, As 2 O 3 inhibits NLRP1, NAIP5/NLRC4 inflammasomes in the same subset of cells (Maier, Crown, Liu, Leppla, & Moayeri, 2014). However, in the human keratinocyte cell line and mouse skin tissue, NaAsO 2 promotes IL‐1β and IL‐18 secretion via AIM2 inflammasome activation (Zhang et al, 2016). In addition, the inflammasome NALP2 polymorphism is associated with arsenic‐induced skin lesions in humans (Bhattacharjee et al, 2013).…”
Section: The Multifaceted Effects Of Trivalent Arsenic On Immune Cellsmentioning
confidence: 99%